DOUBLE ENTRY VOLUMETRIC MODELS EVALUATED FOR Pinus caribeae VAR. hondurensis IN THE COUNTY OF POSSE, GOIÁS, BRAZIL - ANDRADE, Valdir Carlos Lima de; SCHMITT, Thaís (Brazilian Journal of Biometrics, 2016)
This work aimed to evaluate 20 volumetric models for Pinus caribaea var. hondurensis situated in the county of Posse, state of Goiás, Brazil. The information base was composed of 50 sample trees cubed for the use of the Huber’s formula to calculate the real stem volume. Preliminarily, volumetric models were evaluated by the adjusted coefficient of determination, standard error of estimate and graphic analysis of residual waste. Then, the selected models were evaluated per diametric class through statistical criteria: linear correlations and sum of squares of relative residues. It was concluded that the best volumetric models were 3, 14, 15 and 17, among them, the model 14 was developed from the logistic biomathematical model, this was considered the most suitable for use in planting of the species and sampled region.